Effect of maltodextrin concentration on the organoleptic characteristics, proximate composition, and total flavonoid content of instant beras kencur - Iis Ismiati; Mia Srimiati (Sarana Ilmu Indonesia (salnesia), 2025)
Beras kencur (Kaempferia galanga) is a traditional Indonesian herbal beverage with potential to be developed into an instant product through drying technology. This study aimed to analyze the effect of different maltodextrin concentrations on organoleptic characteristics, proximate composition, total flavonoid content, and yield of instant beras kencur produced using the spray-drying method. A completely randomized design (CRD) was employed with three maltodextrin concentrations, namely 20%, 25%, and 30%. The organoleptic evaluation consisted of hedonic and sensory quality tests for both the powder and reconstituted beverage, while proximate and total flavonoid analyses were conducted on the best formulation (P3). The results showed that variations in maltodextrin concentration did not result in significant differences in organoleptic characteristics. The formulation containing 30% maltodextrin (P3) showed the highest mean sensory acceptance, particularly in terms of color and overall acceptance, and was therefore selected as the optimal formulation. The best product was characterized by high water and carbohydrate content. Total flavonoid content slightly decreased after the spray-drying process, from 0.24 ppm before drying to 0.22 ppm after drying. In addition, increasing maltodextrin concentration contributed to a higher yield of instant beras kencur powder.